Qardul Hasan Principles Theory And Implementation In Islamic Banking - Soritua Ahmad Ramdani Harahap; Iza Hanifuddin (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2019)
The qardul hasan contract is one of the contracts to seek the afterlife, because it is not a business contract. So this contract cannot be used for purposes commercial. Islamic banks as an objective financial institution for earning profit cannot rely on tabarru’ contracts for looking for profit. If our goal is to make a profit, use contracts Which is commercial, namely in the contracts. The paper aims to extract Qardul Hasan Principles: Theory and Implementation in Islamic Banking. Understanding qardul hasan will help us determine the action that should or should not be done in performing qardul hasan. It has hoped that this research can contribute to the development of Islamic economics, both in theory and real practice.Keywords: Contract, Qardul Hasan, Islamic Banking